2011
DOI: 10.1371/journal.pgen.1002089
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic and Structural Study of Genome Rearrangements Mediated by High Copy Repeat Ty1 Elements

Abstract: Ty elements are high copy number, dispersed repeated sequences in the Saccharomyces cerevisiae genome known to mediate gross chromosomal rearrangements (GCRs). Here we found that introduction of Ty912, a previously identified Ty1 element, onto the non-essential terminal region of the left arm of chromosome V led to a 380-fold increase in the rate of accumulating GCRs in a wild-type strain. A survey of 48 different mutations identified those that either increased or decreased the rate of Ty-mediated GCRs and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
122
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(132 citation statements)
references
References 71 publications
10
122
0
Order By: Relevance
“…5D). Indeed, GCRs caused by recombination between Ty or delta elements were observed in many previous studies in yeast (33,34).…”
Section: Discussionmentioning
confidence: 77%
“…5D). Indeed, GCRs caused by recombination between Ty or delta elements were observed in many previous studies in yeast (33,34).…”
Section: Discussionmentioning
confidence: 77%
“…44 A large fraction of transposable elements are encoded within telomeric regions, and increased transposition is often associated with telomere dysfunction. 69 We therefore monitored the transposition of a population of endogenous Ty1 transposable elements to an insertion hotspot upstream of SUF16 using a PCR-based assay, 53,54 in SET1-and SET5-mutant cells, as well as strains deleted for other known and putative histone methyltransferases (Fig. 5B).…”
Section: Set1 and Set5 Promote Telomere Maintenance Pathwaysmentioning
confidence: 99%
“…Previous studies of chromosomal rearrangements in budding yeast have shown that many rearrangements occur between dispersed copies of homologous retrotransposon sequences in yeast (Louis and Haber 1990;Fischer et al 2000;Lemoine et al 2005;VanHulle et al 2007;Argueso et al 2008;Chan and Kolodner 2011). We wished to determine how often such sequences would be engaged in template switching in BIR events.…”
Section: Frequent Template Switches Between Naturally Repeated Sequencesmentioning
confidence: 99%